Upaya Menimbulkan dan Mengembangkan Rasa Kepercayaan Diri dalam Siswa/I untuk Mendorong Keaktifan Belajar - Munthe, Yesica Silvia Br (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
Every child needs to have self-confidence, because with self-confidence children can increase their other potentials (Maslow). Many studies reveal that everyone needs self-confidence in the process of self-development. Self-confidence is awareness of one's true potential in doing all things. Therefore, the aim of this writing is to try to create and develop a sense of self-confidence in students in order to encourage active learning in students at school by using the Micro Intervention stage with the Case Work method which has several stages, namely: (1) Engagement intake contact, (2) Assessment, (3) Planning, (4) Intervention, (5) Monitoring, (6) Evaluation, (7) Termination. This practical activity/Field Work Practice (PKL) is a mandatory course that must be carried out and followed by all students in the Social Welfare study program at the Faculty of Social and Political Sciences, University of North Sumatra. This activity was also carried out by the author (Yesica Silvia Br Munthe with NIM 200902082), who is placed at UPT SDN 067247 on Jl. Bunga Malem, Lau Cih, Medan Tuntungan District, Medan City, North Sumatra. Data collection techniques use observation, interviews and documentation methods.